Praktik Penyidikan oleh Polisi dalam Perkara Tindak Pidana Penipuan (Studi Kasus Polres Palu, No: BP-130/2010/RESKRIM) - Siviana, Arina; Rohman, Arif (LPPM Universitas Madako Tolitoli, 2025)
This study aims to identify the obstacles faced by investigators from legal, technical, and administrative aspects, and to assess the extent to which the procedures implemented are in accordance with the provisions of the applicable criminal procedure law. In practice, fraud is often difficult to uncover because the perpetrators often use modes such as promising large profits in a short time, exploiting the psychological weaknesses of the victim, or impersonating authorities to gain trust. This analysis includes an evaluation of the stages of the investigation, starting from reporting the incident, collecting evidence, examining witnesses, to determining the suspect. The results of the study indicate that the effectiveness of the investigation in the case of fraud at the Palu Police, especially in case BP-130/2010/RESKRIM, is influenced by several main factors, namely the completeness of the evidence, the competence of the investigator, and the support of investigation facilities and infrastructure. This study found obstacles in collecting digital evidence used by the perpetrators to deceive the victim. In addition, coordination with related parties, such as forensic experts and banks, succeeded in helping investigators resolve this case to the prosecution stage. These findings indicate that the investigation of fraud cases requires a more adaptive approach and is supported by strengthening the capacity of the police institution.